1984
DOI: 10.1002/aja.1001700316
|View full text |Cite
|
Sign up to set email alerts
|

Gut‐ and bronchus‐associated lymphoid tissue

Abstract: Bronchus-associated and gut-associated lymphoid tissues (BALT and GALT) have both functional and morphologic similarities and are involved in seeding lung, gut, and other mucosal sites with predominantly IgA-containing B cells. Both types of lymphoid tissue are engaged in the regulation and the controlled amplification of immune responses, which vary from positive mucosal responses in both mucosae and peripheral tissues to local mucosal responses and systemic tolerance. Their further involvement in provision o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(64 citation statements)
references
References 62 publications
5
58
0
1
Order By: Relevance
“…This is consistent with human data showing that the BALT is largely absent in healthy adults (47) but becomes apparent following infection and chronic inflammation both in humans and in murine models (4,12,25). The BALT is recognized as a tertiary lymphoid organ (10).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is consistent with human data showing that the BALT is largely absent in healthy adults (47) but becomes apparent following infection and chronic inflammation both in humans and in murine models (4,12,25). The BALT is recognized as a tertiary lymphoid organ (10).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, we report that, following repeated allergen challenge, prominent T cell aggregates and BALT were apparent in CD3-stained sections (Fig. 4B), consistent with the development of these structures in instances of chronic inflammation (4,12,25). The magnitude of these structures increased dose dependently following FTY720 treatment (Fig.…”
Section: Resultssupporting
confidence: 51%
“…Since the oral antigen is taken up through the intestine, the gut-associated lymphoid tissue (GALT) seems to be involved with the induction of oral tolerance. 29) It has been reported that TCRgd-T cells produce the regulatory cytokine transforming growth factor-b1 (TGF-b1) in vitro and induce oral tolerance in vivo, 30) suggesting that the TCRgd-T cells among the IELs produce the regulatory cytokines (TGF-b1 and/or IL-10) upon stimulation and function as regulatory T cells which inhibit antigen-specific T cells. 31) In conclusion, the decrease in the number of gd-IELs caused by anti-TCRgd antibody treatment increased oral sensitization of wild-type (ϩ/ϩ) mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mature BALT is covered by the follicle-associated epithelium (FAE) that harbours numerous lymphocytes (Bienenstock andBefus 1984, Fagerland andArp 1993a). FAE is made up of ciliated and unciliated cells (no goblet cells) and some of them have irregular microvilli on their luminal surface, being in close contact with lymphocytes.…”
Section: Immune Structures In the Respiratory System In Chickens Andmentioning
confidence: 99%